Fluorouracil Supplemented With Oxaliplatin or Irinotecan for Solid Tumors: Indications From Clinical Characteristics and Health Outcomes of Patients - Qingwei, Zhao; Dongsheng, Hong; Duo, Lv; Youlei, Wang; Songxia, Yu; Ziqi, Ye; Lanjuan, Li (Frontiers in Oncology, 2020)
Fluorouracil combined with oxaliplatin (FOLFOX) or irinotecan (FOLFIRI) are both first-line clinical chemotherapy regimens. However, clinicians' selection of FOLFIRI or FOLFOX medication regimens, and their effects on patients' health outcomes are not clear. The aim of this study was to evaluate the impacts of patient characteristics on FOLFIRI or FOLFOX medication regimens selection, and the effects of each regimen on patients’ health outcomes in a real-world setting. 3,725 patients were retrieved and 610 of them were eventually included in this study based on the inclusion and exclusion criteria. The percentages of TNM stages, Cetuximab, Bevacizumab and Tumor metastases between FOLFIRI groups and FOLFOX groups were different (P < 0.001). In the multivariate Cox proportional hazards model, significantly higher non-convalescent incidence in the FOLFOX group was found as compared with the FOLFIRI group (HR, 2.211, 95% CI, 1.257 - 3.888, P = 0.006). In conclusion, TNM staging, whether combined cetuximab or bevacizumab, and whether there was tumor metastasis, presented as the key factors affecting the medication selection between the FOLFIRI and FOLFOX regimens. The FOLFIRI regimen in combination with fluorouracil exhibited better effects on patients' long-term health outcomes than that of the FOLFOX regimen. This study was registered at the World Health Organization International Clinical Trials Registry Platform (ChiCTR2000029201).